Effect of Chinese rice wine sludge on the production of Chinese steamed buns. Issue 4 (30th January 2018) - Ai‐Lati, Aisikaer; Liu, Shuangping; Li, Xiuting; Qian, Bin; Shan, Yunfei; Zhou, Zhilei; Peng, Lin; Ji, Zhongwei; Mao, Jian; Zou, Huijun; Yu, Yongjian; Zhu, Shenghu
Abstract: Chinese rice wine sludge (CRWS), analogous to beer yeast sludge, is the filter cake remaining after squeezing the fermentation mash of Chinese rice wine. CRWS contains high levels of protein (44.74%), nonstructural carbohydrates (37.33%), crude fiber (13.5%), and essential amino acids, which could enhance the trophic value of Chinese steamed buns. In our research, the microbiota of CRWS (mainly Saccharomyces cerevisiae and Lactobacillus sp.) was analyzed at the species level by single‐molecule real‐time DNA sequencing technology. Interestingly, the microbiota of CRWS was similar to that of the starter dough typically used to prepare Chinese steamed buns. Incorporation of CRWS significantly influenced the pasting properties and farinograph characteristics of the dough, which control the texture of the Chinese steamed buns, and supplementation with 5∼30% CRWS caused the properties of the resulting buns to be more similar to those of northern‐style steamed buns. CRWS addition also significantly enhanced the content of aroma compounds in the Chinese steamed buns. Practical applications: In China, approximately three million tons of CRWS is produced per year, and the reutilization of CRWS is a challenge faced by the Chinese rice wine industry. Meanwhile, Chinese steamed buns prepared with CRWS are becoming increasingly popular, and CRWS has been used in the preparation of homemade Chinese steamed buns. However, the use of CRWS in the industrial production of Chinese steamed buns has not yet been developed. The productive use of CRWS could have substantial economic benefits. In this study, the effect of CRWS incorporation on Chinese steamed buns is reported for the first time. The results showed that CRWS improved the quality of Chinese steamed buns. The results of this study suggest a simple and convenient method for incorporating CRWS into the industrial production of northern‐style Chinese steamed buns.